University students, Gender Violence, the Digital Divide and Video Games - Martínez Verdú, Remedios (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2023)
Since the 1960s, when numerous analyses of the culture of contemporary society, in which video games are integrated, have been carried out, they have been increasingly conceived as a cultural product, in contrast to those approaches that have tended to highlight the video game as a technological element. From the perspective of the Frankfurt School,which coined and developed the concept of cultural industry, video games produce and reproduce certain values and ideas of modern society and are immersed in the so-called phenomenon of gamification.